The Influence of Celebrity Endorsement, Content Marketing, and Brand Trust on Generation Z’s Purchase Intention in Shopee - Praba Phatriscia; Audita Nuvriasari (Arthatama: Journal of Business Management and Accounting, 2025)
The rapid growth of e-commerce has intensified competition among skincare brands on Shopee, where Generation Z represents a significant consumer segment. Understanding the determinants of their purchase intention is essential for developing effective digital marketing strategies. This study aims to examine the influence of celebrity endorsement, content marketing, and brand trust on Generation Z’s purchase intention toward skincare products on Shopee. A quantitative approach was employed using a survey of 100 respondents selected through non-probability sampling. Data were collected using a structured questionnaire and analyzed using multiple linear regression. The results confirmed that all instruments were valid and reliable, and the classical assumption tests indicated that the data were normally distributed and free from multicollinearity and heteroscedasticity. The findings show that celebrity endorsement and brand trust have a positive and significant effect on purchase intention, while content marketing does not significantly influence purchase intention. These results highlight the importance of credible endorsers and strong brand trust in shaping Generation Z’s purchasing decisions. The study provides practical insights for skincare brands to prioritize trust-building strategies and effective endorsement in online marketplaces.